2020
DOI: 10.1101/2020.07.27.223693
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ERβ regulated ovarian kisspeptin plays an important role in oocyte maturation

Abstract: Kisspeptin (KISS1) signaling in the hypothalamic-pituitary (H-P) axis plays essential role in regulating gonadotropin secretion. KISS1 and KISS1 receptor (KISS1R) are also expressed in the ovary; however, the role of intraovarian KISS1 signaling remains largely unclear. Granulosa cell (GC)-specific expression of KISS1, and oocyte-specific expression of KISS1R indicate that GC-derived KISS1 may act on oocytes. Expression of KISS1 in GCs is induced by gonadotropins but it is absent in estrogen receptor β knockou… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Despite an increased expression of FSHR, administration of PMSG fails to induce the genes required for an effective LH response [ 101 , 128 ]. Although there was no change in FSH-induced genes such as Star , expression of Lhcgr , Cyp11a1 , Cyp19a1 , Gata4 , and Npr2 failed to upregulate in Erβ KO GCs [ 10 , 100 , 101 , 129 ] ( Figure 5 ). These findings suggest that expression of a subset of FSH-induced genes is dependent on the presence of ERβ in GCs [ 101 ].…”
Section: Erβ Regulation Of the Gonadotropin Responsesmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite an increased expression of FSHR, administration of PMSG fails to induce the genes required for an effective LH response [ 101 , 128 ]. Although there was no change in FSH-induced genes such as Star , expression of Lhcgr , Cyp11a1 , Cyp19a1 , Gata4 , and Npr2 failed to upregulate in Erβ KO GCs [ 10 , 100 , 101 , 129 ] ( Figure 5 ). These findings suggest that expression of a subset of FSH-induced genes is dependent on the presence of ERβ in GCs [ 101 ].…”
Section: Erβ Regulation Of the Gonadotropin Responsesmentioning
confidence: 99%
“…However, the molecular mechanism underlying such reduced cAMP production in GCs remains unclear [ 79 ]. In vitro and in vivo studies have also demonstrated defective antrum formation, associated with decreased cumulus expansion after FSH treatment [ 120 , 129 , 130 ]. Due to the reduced levels of Cyp11a1 and Cyp19a1 , GCs in Erβ KO preovulatory follicles exhibit significantly lower levels of FSH-induced estrogen synthesis [ 120 , 130 ].…”
Section: Erβ Regulation Of the Gonadotropin Responsesmentioning
confidence: 99%
See 2 more Smart Citations